Smart contracts in Mexican law: challenges and opportunities for their integration into the legal framework - Cuautle Miguel, Felipe Alejandro (2023)
This article addresses the challenges and opportunities presented by smart contracts in the Mexican legal framework, for which its legal nature, essential elements, and validity requirements will be analyzed. It also highlights the importance of adapting the Federal Civil Code to the particularities of this technology and proposes some legislative amendments that could facilitate its integration into the legal framework.